An analytical method for selecting the optimal nozzle external geometry for fluid dynamic gauging - Peralta, Juan Manuel (2011)
Fluid dynamic gauging (FDG) was developed to measure, in situ and in real time, the thickness of a soft deposit layer immersed in a liquid without contacting the surface of the layer. An analysis based on the lubrication assumption for the flow patterns in the space between the nozzle and the surface being gauged yielded analytical expressions for the relationships between the main flow variables and system parameters. Nozzle shapes for particular pressure, pressure gradient and shear stress profiles could then be identified. The effect of flow rate, nozzle geometry and nozzle position on the pressure beneath the nozzle and shear stress on the gauged surface showed very good agreement with computational fluid dynamics (CFD) simulations. Case studies presented include nozzle shapes for uniform pressure and shear stress profiles, which are useful for measuring the strength of soft deposit layers.